2007
DOI: 10.1002/cpp.516
|View full text |Cite
|
Sign up to set email alerts
|

Designing a CBT service for an acute inpatient setting: A pilot evaluation study

Abstract: A frequent complaint by service-users of psychiatric inpatient units is the unavailability of talking therapy at precisely the time when they need to make sense of their situation. However, conventional models of cognitive-behavioural therapy (CBT) delivery, with set numbers of sessions and diagnostic specificity, are not well suited to the conditions of the acute ward, with variable and unpredictable lengths of stay and multiple and indistinct presentations. This pilot study describes a modification of CBT de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 25 publications
0
26
1
1
Order By: Relevance
“…The findings of our study suggest that a large minority of psychotic inpatients may be expressly interested in therapy, which provides support for the introduction of CBT during a hospital admission (Durrant, Clarke, Tolland, & Wilson, 2007;National Institute for Clinical Excellence, 2009). Further, we were able to uncover a number of reasons why patients in hospital might be interested in receiving therapy.…”
Section: Discussionmentioning
confidence: 91%
“…The findings of our study suggest that a large minority of psychotic inpatients may be expressly interested in therapy, which provides support for the introduction of CBT during a hospital admission (Durrant, Clarke, Tolland, & Wilson, 2007;National Institute for Clinical Excellence, 2009). Further, we were able to uncover a number of reasons why patients in hospital might be interested in receiving therapy.…”
Section: Discussionmentioning
confidence: 91%
“…We have shown that individual therapy sessions can be delivered with relative ease in the acute environment, whereas, in contrast to previous work (Araci & Clarke, ; Durrant et al ., ), delivery of group interventions was challenging. This disparity may be due to reliance on ward staff nurses or less resource from the psychological team to deliver groups.…”
Section: Discussionmentioning
confidence: 99%
“…In vocational rehabilitation studies of persons who are chronically ill and homeless, the PES can assess the lack of resources and unmet needs (2). The MHCS will fit well in studies aimed at the effect of treatment in interventions, such as peer support groups (15), dual-focus self-help groups (16), and cognitive-behavioral therapy (17), but it does not measure societal empowerment.…”
Section: Discussionmentioning
confidence: 99%